John 1-12 - Farmer, Craig S. (Craig Steven), 1961- (Downers Grove, IL : InterVarsity Press, 2014)
The first eighteen verses of the Gospel of John make some of the most profound statements about the character and work of Christ in all of Scripture: "In the beginning was the Word, and the Word was with God, and the Word was God" (1:1); "all things were made through him" (1:3); "the Word became flesh and dwelt among us" (1:14). Reformation commentators ruminated on the meaning and implications of such claims for shedding light on doctrines like the Trinity, the divinity of Christ and his incarnation, but also for grasping the saving benefits of Christ's work in justification (for those "who believed in his name") and new birth (those born of God as his children, 1:12-13). In this volume, Craig Farmer guides readers through Reformation meditation on these themes and many others as they are unpacked in the first twelve chapters of the Gospel of John, from the Prologue to Jesus' triumphal entry into Jerusalem. Here you will find a mosaic of reflection on the Gospel of John by a variety of significant well-known and lesser-known figures among the Reformed, Lutherans, Radicals and Roman Catholics. Farmer has done justice to the depth and nuance of the work of these Reformation-era pastors and scholars by drawing from a range of genres--extensive commentary, brief annotations, impassioned sermons, official confessions, and careful doctrinal and practical treatises. --From publisher's description.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 630
Keywords: Bible. -- Commentaries; RELIGION -- Biblical Studies -- Jesus, the Gospels & Acts; RELIGION -- Biblical Studies -- New Testament; Electronic books